Assessment of Electric Field Distribution Inside 500/220 kV Open Distribution Substations During Working Conditions - Sayed A. Ward; Samy M. Ghania; Essam M. Shaalan (Institute of Advanced Engineering and Science, 2014)
The high level electric field intensity produced by high voltage (HV) equipments inside 500/220 kV substations is harmful for the human (staff) health. Therefore the minimum health and safety requirements regarding the exposure of workers to the risk arising from electric fields produced inside these substations is still considered as a competitive topic for utility designers, world health organization (WHO) and biomedical field researchers. It is very important to have knowledge about levels distribution of electric field intensity within these high voltage substations as early stage in the process of substation design. This paper presents results of investigation 50Hz electric field intensity distribution inside 500/220 kV power transmission substations in Cairo, Egypt. This paper presents a method for assessment the distribution of 50HZ electric field intensity distribution inside this substation, this method of analysis is based on the charge simulation technique (CSM). This study will serve for planning service works or for inspection of equipment on HV power transmission substations.